2009
DOI: 10.1002/jrs.2524
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and pH dependent SERS spectra of sulfanilic acid sodium salt on colloidal silver particles

Abstract: IR, Raman and surface-enhanced Raman scattering (SERS) spectra of sulfanilic acid sodium salt (SANA) were recorded and analysed. The vibrational wavenumbers were computed by the density functional theory method using the B3LYP/6-31G * basis and found to be in good agreement with the experimental values. The effect of concentration and pH dependence on the SERS intensity of the molecule was also studied. The molecular plane assumes a tilted orientation with respect to the silver surface. The observed changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Also studied and analyzed by Panicker and coworkers were 2-[acetyl(4-bromophenyl)carbamoyl]-4-chlorophenyl acetate, [263] 4-ethyl-N-(2-hydroxy-5-nitrophenyl)benzamide, [264] and sulfanilic acid sodium salt. [265] Special Issues and Reviews…”
Section: Methods Of Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also studied and analyzed by Panicker and coworkers were 2-[acetyl(4-bromophenyl)carbamoyl]-4-chlorophenyl acetate, [263] 4-ethyl-N-(2-hydroxy-5-nitrophenyl)benzamide, [264] and sulfanilic acid sodium salt. [265] Special Issues and Reviews…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…The vibrational wavenumbers were computed using HF/6‐31G* and DFT/B3LYP/6‐31G* model chemistries. Also studied and analyzed by Panicker and coworkers were 2‐[acetyl(4‐bromophenyl)carbamoyl]‐4‐chlorophenyl acetate, 4‐ethyl‐ N ‐(2‐hydroxy‐5‐nitrophenyl)benzamide, and sulfanilic acid sodium salt …”
Section: Vibrational Studies In Chemistrymentioning
confidence: 99%
“…Surface‐enhanced Raman scattering (SERS) is one of the most sensitive techniques for probing interfacial reactions occurring on metal surfaces . SERS can also be used to study pH‐dependent behaviors . SERS has high sensitivity, but its intensity may be significantly changed depending on the surface distances .…”
Section: Introductionmentioning
confidence: 99%
“…[1] SERS can also be used to study pH-dependent behaviors. [2][3][4][5] SERS has high sensitivity, but its intensity may be significantly changed depending on the surface distances. [6] For this reason, simple desorption reactions are conducted using labeled Raman dyes such as para-aminothiophenol and Nile Blue because of the rather drastic change of the local enhancements from the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…pH is also an important parameter in SERS study. Reports have demonstrated that the Raman enhancement induced by Ag or Au nanoparticles is affected by the pH value of the solution because of different adsorption behavior of molecules on nanoparticles at various pH values . However, whether the SERS effect caused by GO can be affected by pH is still unknown.…”
Section: Introductionmentioning
confidence: 99%